The Impact of Farm Production Factors on The Income of Horticultural Farmers in East Java - Pariasa, Imaniar Ilmi; Hardana, Andrean Eka (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
In agricultural growth, the horticulture subsector holds a crucial place. However, one of the most common and productive challenges that farmers deal with is capital limits. Lack of financing is frequently cited as a barrier to addressing rising production costs and erratic commodities selling prices. Financing for factors of production becomes challenging as a result. This study aims to analyze the influence of farm production factors on the income of horticultural farmers in East Java. Data collection was conducted in two locations, namely Wonomulyo Village, Poncokusumo District, Malang Regency, and Pacet Village, Pacet District, Mojokerto Regency. These two locations were chosen purposefully because they are horticulturally producing centers in East Java with the most financial institutions, with a total of 160 respondents. Data collection methods can include interviews using a questionnaire tool. To fulfill the research objective, multiple regression analysis has been used. The land area variable has the most influence since income and land area interact in such a way that as land area is utilized, revenue rises accordingly. The data indicates that there is a positive significance between land area and income in East Java's horticulture farms. Farmers need to seek to intensify horticulture to increase production on existing land with a farming venture. As well as the development of the agribusiness system through Cooperative Farming.